Soil variability effects on the yield of winter wheat under variable-rate nitrogen applications - Miles, Daniel (Cranfield University, 2016)
Seven UK fields located across Oxfordshire, Southampton and W. Berkshire, five cropped in winter wheat in 2014 and two in 2013 were investigated to assess the effect of soil variability on mean yield and yield variance under flat-rate and variable- rate nitrogen applications. The high level aim being to provide information to help guide growers on how best to apply nitrogen fertiliser to increase yield and enhance yield uniformity. Data layers were collated for shallow Electrical-Conductivity (EC), Leaf Area Index, nitrogen application and yield. Yields were neither significantly higher under flat-rate nor variable-rate treatment (p = 0.8356). Variation in shallow EC was neither significantly more different in the variable-rate treatments or the flat- rate treatments (p = 0.7862). Variability in EC held a positive relationship with yield variability under both flat-rate (R2 = 0.2102) (p = 0.0213) and variable-rate treatment (R2 = 0.1507) (p = 0.0176). This suggests that variable-rate treatment provided no significant benefit in reducing yield variability.
Keywords: Precision farming; GPS; Fertiliser; UK agriculture; Remote sensing